2007
DOI: 10.3386/w13614
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Income Effect: Gasoline Prices and Grocery Purchases

Abstract: This paper examines the importance of income effects in purchase decisions for everyday products by analyzing the effect of gasoline prices on grocery expenditures. Using detailed scanner data from a large grocery chain as well as data from the Consumer Expenditure Survey (CES), we show that consumers re-allocate their expenditures across and within food-consumption categories in order to offset necessary increases in gasoline expenditures when gasoline prices rise. We show that gasoline expenditures rise one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 49 publications
4
25
0
Order By: Relevance
“…Other studies have also found similar results (Espey, 1996;Small and Van Dender, 2007). Using Consumer Expenditure Survey data, Cooper, 2005 andGicheva et al, 2007 Oladosu (2003) found that only the newest vehicle in a household with multiple vehicles is expenditure inelastic. A number of other disaggregate-level studies have also looked at the impact of higher fuel price on household vehicle composition and usage.…”
Section: Understanding Transportation-related Consumer Expendituressupporting
confidence: 66%
See 1 more Smart Citation
“…Other studies have also found similar results (Espey, 1996;Small and Van Dender, 2007). Using Consumer Expenditure Survey data, Cooper, 2005 andGicheva et al, 2007 Oladosu (2003) found that only the newest vehicle in a household with multiple vehicles is expenditure inelastic. A number of other disaggregate-level studies have also looked at the impact of higher fuel price on household vehicle composition and usage.…”
Section: Understanding Transportation-related Consumer Expendituressupporting
confidence: 66%
“…Thus, a positive (negative) coefficient for a certain variable-category combination means that an increase in the explanatory variable increases (decreases) the likelihood of budget being allocated to that expenditure category relative to the base expenditure categories. For example, as household size increases, the proportion of total income share expended on food increases relative to other categories (see Gicheva et al, 2007 for a similar result). This is also true for the income share spent on utilities, while the income share expended on housing tends to decrease with an increase in household size.…”
Section: Model Estimation Resultsmentioning
confidence: 56%
“…For example, the shift in grocery shopping towards private labels in economically more difficult times has been documented in, among others, Deleersnyder et al (2009), Lamey (2014, Lamey et al (2007Lamey et al ( , 2012, Ma et al (2011), andDubé et al (2017). Within the service industry, (international) tourism has been subjected to an elaborate BC analysis in Kumar et al (2014), Dekimpe et al (2016), and Peers et al (2017), and the impact of changing gasoline prices on grocery shopping has been studied in Ma et al (2011) and Gicheva et al (2010), among others. Given the different research methods adopted in some of these studies, this either increases one's confidence in the findings in case comparable conclusions are reached (as then the power of diverse methods is harnessed; Hamilton 2016), or can stir an interesting debate if not.…”
Section: Broadening the Research Scopementioning
confidence: 99%
“…We regress this measure of private label share on a local zipcode level measure of median household income from the 2000 Census and local (MSA or county level) measures of time-varying gas prices and unemployment rates; following Gicheva et al (2010) we interpret a rise in gas prices as a negative disposable income shock to households given the very low price elasticity of gasoline. Table 8 presents our results.…”
Section: Macroeconomic Implicationsmentioning
confidence: 99%